Variable range hopping conduction in fully dense calcium cobalt oxide textured ceramics. Issue 13 (September 2018) - Puri, Nidhi; Tandon, Ram P.; Mahapatro, Ajit K.
Abstract: Fully dense hot-pressed calcium cobalt oxide (Ca3 Co4 O9 ) pellet exhibits textures with Lotgering factor of unity and supports the ideally aligned (00  l ), l = 2, 3, 4, 5 crystallographic planes associated in the ceramics. The DC electrical conductivity of the Ca3 Co4 O9 pellets connected to metal/Ca3 Co4 O9 -pellet/metal device structures in vertical and lateral configurations follow Mott's variable range hopping. The exhibition of anisotropic ratio of ~ 10 between the room temperature conductivity values in both the structures, reveal the presence of partially oriented textured grains in the currently developed Ca3 Co4 O9 ceramics. Graphical abstract: fx1